THE POTENTIAL OF LOCAL BRANDING IN THE ECONOMIC PERFORMANCE OF AGRO-PROCESSING INDUSTRIES AND AGROTOURISM IN VLORA, ALBANIA - Polaj, Edvina; Kadiu, Edmond; Pepkolaj, Lekë (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the influence of branding on the economic performance of agricultural-livestock agro-processing industries and agrotourism enterprises in the Vlora region, emphasizing two performance indicators: Performance 1 (revenue growth) and Performance 2 (financial improvement). The research aims to verify the relationship between the agro-processing sector and the development of agritourism by analyzing how branding and the marketing of locally indicated products enhance economic outcomes. Data were collected from over 100 agro-processing industries and agrotourism businesses and analyzed using the STATA software. The findings reveal that branding has a significant positive effect on financial performance, with revenue increasing from 1,111 to 2,593 after implementing branding strategies. Furthermore, the marketing of branded products is linked to a notable rise in tourist numbers—an average of 2,815 compared to 2,640 in non-branded businesses—demonstrating that brand identity strengthens the competitiveness and attractiveness of agrotourism destinations. The novelty of this study lies in its integration of branding analysis within the dual framework of agro-processing and agritourism, highlighting branding as both an economic and cultural lever for rural development. Unlike previous studies that examined these sectors separately, this research provides empirical evidence of branding’s role as a bridge between local product identity and sustainable tourism growth. These results underscore the strategic importance of investing in brand development to enhance rural economic resilience, promote value-added agricultural products, and stimulate regional economic development through the synergy of agriculture, industry, and tourism.